#### Answer

The solution set for this inequality is $(-∞, 0)$.

#### Work Step by Step

To solve the inequality, we need to isolate variables on one side of the inequality and the constants on the other side.
First, let's use distributive property:
$$6x - 3 \leq 3(x) - 3(1)$$
Multiply:
$$6x - 3 \leq 3x - 3$$
Subtract $3x$ from both sides of the inequality to isolate the variable to one side of the inequality:
$$(6x - 3x) - 3 \leq (3x - 3x) - 3$$
Let's do the subtraction:
$$3x - 3 \leq -3$$
Let's add $3$ to each side of the inequality to isolate the constants on one side of the inequality:
$$3x \leq 0$$
Divide by $3$ on each side of the inequality:
$$x \leq 0$$
The solution set for this inequality is $(-∞, 0)$.